Using signal detection theory in the analysis of emotional sensitivity of male recidivist offenders. (10th March 2015) - Barbosa, Fernando; Almeida, Pedro R.; Ferreira‐Santos, Fernando; Marques‐Teixeira, João
Abstract: Background: Study of emotional responses of antisocial individuals has produced inconsistent findings. Some studies report emotional deficits, while others find no differences between people with and without antisocial behaviours. Aims: Our aim was to apply signal detection theory methods to compare the sensitivity of antisocial and control participants to emotional stimuli. We hypothesised that offenders would show lower ability to discriminate changes in the level of arousal and valence of emotional stimuli relative to the controls. Methods: Signal detection theory was applied to study the sensitivity of recidivist offenders in prison to emotional arousal and valence induced by pictures. This approach, novel in this context, provides a departure from the usual reliance on self‐report. Results: Offenders reported higher arousal than controls but showed lower sensitivity to changes between different levels of arousal (whereas no differences were found for valence). Also, offenders showed increased response bias for changes in the levels of arousal, as well as in the higher levels of valence. Conclusions: Our findings show that direct observations of emotional arousal, but not valence, discriminate between recidivist offenders with antisocial personality disorder and non‐offending controls. Use of such approaches is likely to provide more valid data than self‐reports and may prove particularly useful in studies of intervention for recidivists or in assessment of their readiness for release. Copyright © 2015 John Wiley & Sons, Ltd.